Embedded GaN nanostripes on c‐sapphire for DFB lasers with semipolar quantum wells. Issue 1 (14th August 2015) - Leute, Robert A. R.; Heinz, Dominik; Wang, Junjun; Meisch, Tobias; Müller, Marcus; Schmidt, Gordon; Metzner, Sebastian; Veit, Peter; Bertram, Frank; Christen, Jürgen; Martens, Martin; Wernicke, Tim; et al.
Abstract: GaN based laser diodes with semipolar quantum wells are typically grown on free‐standing pseudo‐substrates of small size. We present an approach to create a distributed‐feedback (DFB) laser with semipolar quantum wells (QWs) on c ‐oriented templates. The templates are based on 2‐inch sapphire wafers, the method could easily be adapted to larger diameters which are available commercially. GaN nanostripes with triangular cross‐section are grown by selective area epitaxy (SAE) and QWs are grown on their semipolar side facets. The nanostripes are completely embedded and can be sandwiched inside a waveguide. For optical pumping, open waveguide structures with only a bottom cladding are used. Using nanoimprint lithography, stripe masks with 250 nm periodicity were fabricated over the whole wafer area. The periodicity corresponds to a 3rd order DFB structure for a laser emitting in the blue wavelength regime. These samples were analyzed structurally by high‐resolution transmission electron microscopy (HRTEM), and spatio‐spectrally by cathodoluminescence (CL) inside a scanning transmission electron microscope (STEM). Samples with an undoped cap are pumped optically for stimulated emission. To prove the feasibility of realizing a 2nd order DFB structure with this approach, stripes with a 170 nm periodicity are fabricated by electron beam lithography and SAE.